Bolometric luminosity estimators using infrared hydrogen lines for dust obscured active galactic nuclei. Issue 1 (25th October 2021) - Kim, Dohyeong; Lee, Daye; Im, Myungshin
ABSTRACT: Bolometric luminosity is an important quantity that tells us the radiative energy output of an active galactic nucleus (AGN). A common way to estimate bolometric luminosity is to use ultraviolet (UV) or optical luminosities as its proxies, but the UV- or optical-based-bolometric luminosity estimators can be easily affected by dust extinction. In this study, we present new methods for estimating bolometric luminosities using infrared (IR) hydrogen Paschen and Brackett line luminosities to alleviate the dust extinction effects. We show that there exist tight correlations between the bolometric luminosities and the IR hydrogen line luminosities, and present the IR hydrogen line-based-bolometric luminosity estimators. As an example, we apply the relation to dust obscured red AGNs, confirming previous results that red AGNs have higher Eddington rations than unobscured AGNs. The new bolometric luminosity estimator will be useful for studying obscured AGNs (e.g. red AGNs, Compton thick AGNs, and Type 2 AGNs), during the coming era of sensitive near-infrared (NIR) and mid-infrared (MIR) missions, such as the James Webb Space Telescope .